Applying Input-output Model to Estimate the Broader Economic Benefits of Cipularang Tollroad Investment to Bandung District. (2015) - Anas, Ridwan; Tamin, Ofyar Z.; Wibowo, Sony S.
Abstract: This paper aims to estimate the potential economic benefits of an individual transportation project (Cipularang Tollroad) investment to the regional economy of Bandung district by using input-output analysis. The linkage between transportation investment and economic growth has been widely researched in the past 25 years. Most research confirm that the improvement of transportation performance through transportation investment can reduce logistic cost of the production sectors and thus reducing their marginal cost. Consequently, the increase of the output in the production sectors is expected to develop the regional economy. Compared to other Asian countries, logistics cost in Indonesia is much higher than that of other nations in the region. Reaching up to 25% of the Gross Domestic Product (GDP), this cost causes the production sectors to become inefficient and less competitive (LPEM- UI, year). The purpose of this study was to estimate the broader economic benefits of the new infrastructure investment of Cipularang Tollroad to Bandung region that region connected to the tollway. Specifically, this study mapped out the indirect benefits received by the production sector (key sectors) in relation to the associated decrease of freight transportation costs. This study found that industrial served as the key sectors in Bandung district region. Using the regional input-output simulation model, the regional GDP increases 1% after the operation of Cipularang Tollroad. This increase was estimated due to reduce of inter-regional freight transportation costs. This study has implications for the stakeholders involved in the development of Indonesian transportation infrastructure, by highlighting the broader economic benefits received by the regions (especially key sector) in which the transportation project investment occurs.